INVESTIGATION OF AREAS OF NON-CONTACT IMPACT ON LAND AND BUILDINGS - I. N. Abdullaev; Yunusaliev E.M (Journals Park Publishing, 2023)
A description of the waves that occur in the ground when using the proposed non-contact shock method for testing the seismic resistance of buildings and structures during operation is presented.
Keywords: earthquake resistance of buildings and structures, impact equipment, detonation, fuel mixture, shock zones, shock waves.